Exploring AI-Powered Speaking Applications on Learning Styles Accommodation Among Indonesian Senior High School Students - Cut Miftahul Salami; Muhammad Dalimunte; Farida Repelita Waty BR Kembaren (MASI Mandiri Edukasi, 2026)
This qualitative case study addresses the understudied interplay between students' diverse VARK learning styles (Visual, Auditory, Read/Write, Kinesthetic) and their engagement with an integrated AI-powered speaking platform, Practica AI, within the Indonesian socio-cultural context. The research was driven by the practical observation of varied learning outcomes among students using the same AI tool, suggesting a critical mediating role of individual learning styles. Conducted over three months at SMA Sukma Bangsa Lhokseumawe, the study employed a descriptive case study design with six purposefully selected 10th-grade participants representing a spectrum of VARK profiles. Data were collected through semi-structured interviews, non-participant observations, participant reflective journals, and document analysis (VARK questionnaires, app logs). Thematic analysis revealed three primary findings. First, learning styles functioned not as static labels but as dynamic strategic identities; students consciously curated personalized learning pathways by selectively navigating and combining Practica AI's multimodal features. Second, the study conceptualizes a critical